2014
DOI: 10.1371/journal.pone.0094159
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Mediated Gene Transfer of the Obesity-Associated Gene Etv5 in Rat Midbrain Does Not Affect Energy Balance or Motivated Behavior

Abstract: Several genome-wide association studies have implicated the transcription factor E-twenty- six version 5 (Etv5) in the regulation of body mass index. Further substantiating the role of Etv5 in feeding behavior are the findings that targeted disruption of Etv5 in mice leads to decreased body weight gain and that expression of Etv5 is decreased in the ventral tegmental area and substantia nigra pars compacta (VTA/SNpc) after food restriction. As Etv5 has been suggested to influence dopaminergic neurotransmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Ets variant 5 ( ETV5 , also known as ERM), an E-twenty-six (ETS) transcription factor belonging to the polyoma enhancer activator 3 (PEA3)-subfamily ( ETV1 , ETV4 and ETV5 ), was initially linked to BMI in a GWAS study [ 8 ]. Experimental evidence in mice also links Etv5 to the regulation of metabolic homeostasis; Etv5 transcriptional expression is affected by ingestion of a high-fat/high-sugar diet, as well as food restriction [ 9 , 10 ]. Moreover, Etv5 -/- mice exhibit decreased body weight compared to controls [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ets variant 5 ( ETV5 , also known as ERM), an E-twenty-six (ETS) transcription factor belonging to the polyoma enhancer activator 3 (PEA3)-subfamily ( ETV1 , ETV4 and ETV5 ), was initially linked to BMI in a GWAS study [ 8 ]. Experimental evidence in mice also links Etv5 to the regulation of metabolic homeostasis; Etv5 transcriptional expression is affected by ingestion of a high-fat/high-sugar diet, as well as food restriction [ 9 , 10 ]. Moreover, Etv5 -/- mice exhibit decreased body weight compared to controls [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence in mice also links Etv5 to the regulation of metabolic homeostasis; Etv5 transcriptional expression is affected by ingestion of a high-fat/high-sugar diet, as well as food restriction [ 9 , 10 ]. Moreover, Etv5 -/- mice exhibit decreased body weight compared to controls [ 9 , 10 ]. In mouse brain, Etv5 is expressed in the arcuate nucleus (ARC), ventro-medial hypothalamus (VMH), substantia nigra (SN), and the ventral tegmental area (VTA) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primer sequences are listed in S1 File . The synthesis of 33 P RNA-probes and in situ hybridization were performed as described in previous work [ 34 ]. Briefly, sections were hybridized to the 1 x 10 6 cpm of anti-sense 33 P RNA probe in 150 μL hybridization mixture with 50% deionized formamide, 2x standard saline citrate (SSC), 10% dextrane sulphate, 1x Denhardt’s solution, 5 mM ethylenediaminetetraacetic acid (EDTA), and 10 mM phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Etv5-/-mice have been shown to have reduced body weights compared with wild-type controls [179]. In addition, the nutritional state has been shown in animal models to affect the expression of Etv5 in important areas for feeding behavior [180], although this overexpression did not translate into significant changes of eating habits [181]. In any case, it has been suggested that, being a transcription factor, the possibility that ETV5 influences energy balance by transcriptional regulation of key genes linked to food intake in the hypothalamus seems highly likely [161].…”
Section: Etv5 Transcription Factormentioning
confidence: 99%